2021
DOI: 10.3390/su13052713
|View full text |Cite|
|
Sign up to set email alerts
|

Household-Level Determinants of Participation in Forest Support Programmes in the Miombo Landscapes, Zambia

Abstract: The need to protect forest resources from unsustainable, yet rational, human actions has attracted global attention. This is because smallholder dependence on forests can degrade forest resources and cause deforestation. While efforts to understand forest programmes and motivations to protect forests have increased in recent decades, there remains a limited understanding of household factors affecting participation in forest support programmes, especially in the context of high-pressure areas, such as the Miom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Issues that relate to the factors that influence people's involvement in forest management programs need to be studied to determine the appropriate interventions [30]. Rural-based households in Zimbabwe encounter many hurdles to come out with relevant and applicable ways to cope with climate change impacts [8].…”
Section: Discussion Of Agroforestry As a Small Landholder Toolmentioning
confidence: 99%
See 2 more Smart Citations
“…Issues that relate to the factors that influence people's involvement in forest management programs need to be studied to determine the appropriate interventions [30]. Rural-based households in Zimbabwe encounter many hurdles to come out with relevant and applicable ways to cope with climate change impacts [8].…”
Section: Discussion Of Agroforestry As a Small Landholder Toolmentioning
confidence: 99%
“…The challenge of deforestation has been exacerbated by the lack of corresponding efforts in reforestation. So, even though vegetation is a renewable natural resource, the rate at which regeneration of trees and other components of the ecosystem that survive after the damage is lower than the rate of the loss is incurred [30]. Massive biodiversity loss follows.…”
Section: Smallholder Agriculture and Its Impact On Forest Resources In Zimbabwementioning
confidence: 99%
See 1 more Smart Citation
“…Forest products are a source of income for rural areas, as evidenced by the fact that rural people continue to rely on them for income. Kazungu et al, (2021) contended that, tropical and subtropical forest landscapes support the livelihoods of their inhabitants through subsistence use of goods and financial gain through product sales. Forest products provide for an average of 20.6 percent of total household income (subsistence and cash) at the eight sites studied, and are the second or first source of income in five of them.…”
Section: Factors Affecting Land-use Changementioning
confidence: 99%
“…According to Suleiman et al (2017), large families have limited land holdings and high food dependency ratios, so they rely on natural resource collection due to the availability of family labour. Older household heads are more likely to participate in natural resource collection because it improves their livelihood opportunities (Kazungu et al, 2021). Studies also found that membership in forest products-related groups or any social network is critical for exchanging information between members and even the pursuit of a common goal (Suleiman et…”
Section: Empirical Analysismentioning
confidence: 99%